The MCT1 gene Glu490Asp polymorphism (rs1049434) is associated with endurance athlete status, lower blood lactate accumulation and higher maximum oxygen uptake - Guilherme, J.; Bosnyák, E.; Semenova, E.; Szmodis, M.; Griff, A.; Móra, Á.; Almási, G.; Trájer, E.; Udvardy, A.; Kostryukova, E. S.; Borisov, O. V.; Larin, A. K.; et al. (Biology of Sport, 2021)
The purpose of this study was to explore the association of the MCT1 gene Glu490Asp polymorphism (rs1049434) with athletic status and performance of endurance athletes. A total of 1,208 Brazilians (318 endurance athletes and 890 non-athletes) and 867 Europeans (315 endurance athletes and 552 non-athletes) were evaluated in a case-control approach. Brazilian participants were classified based on self-declared ethnicity to test whether the polymorphism was different between Caucasians and Afro-descendants. Moreover, 66 Hungarian athletes underwent an incremental test until exhaustion to assess blood lactate levels, while 46 Russian athletes had their maximum oxygen uptake (O2max) compared between genotypes. In the Brazilian cohort, the major T-allele was more frequent in Caucasian top-level competitors compared to their counterparts of lower competitive level (P = 0.039), and in Afro-descendant athletes compared to non-athletes (P = 0.015). Similarly, the T-allele was more frequent in European athletes (P = 0.029). Meta-analysis of the Brazilian and European cohorts confirmed that the T-allele is over-represented in endurance athletes (OR: 1.48, P = 0.03), especially when Afro-descendant athletes were included in the meta-analysis (OR: 1.58, P = 0.005). Furthermore, carriers of the T/T genotype accumulated less blood lactate in response to intense effort (P<0.01) and exhibited higher O2max (P = 0.04). In conclusion, the Glu490Asp polymorphism was associated with endurance athletic status and performance. Our findings suggest that, although ethnic differences may exist, the presence of the major T-allele (i.e., the Glu-490 allele) favours endurance performance more than the mutant A-allele (i.e., the 490-Asp allele).